2008
DOI: 10.1136/bjo.2007.128769
|View full text |Cite
|
Sign up to set email alerts
|

Leptin increases in Vogt-Koyanagi-Harada (VKH) disease and promotes cell proliferation and inflammatory cytokine secretion

Abstract: These findings suggest that leptin may be involved in the development of VKH disease possibly by promoting an immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
(30 reference statements)
1
13
1
Order By: Relevance
“…20 Moreover, some recent studies indicate that leptin and MIF might also stimulate the expression of IL-17 in human and mouse mononuclear cells, respectively. 18,19 Our results, however, argue against the possibility that such a link might be operative in human obesity, as no correlation was observed between the levels of IL-17 or IL-23 and those of leptin or MIF in obese women. On the other hand, IL-17 showed a clear tendency toward positive correlation with IL-23 in obese subjects, which is consistent with the well-known role of IL-23 in inducing IL-17 secretion in T lymphocytes and other cell types.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…20 Moreover, some recent studies indicate that leptin and MIF might also stimulate the expression of IL-17 in human and mouse mononuclear cells, respectively. 18,19 Our results, however, argue against the possibility that such a link might be operative in human obesity, as no correlation was observed between the levels of IL-17 or IL-23 and those of leptin or MIF in obese women. On the other hand, IL-17 showed a clear tendency toward positive correlation with IL-23 in obese subjects, which is consistent with the well-known role of IL-23 in inducing IL-17 secretion in T lymphocytes and other cell types.…”
Section: Discussioncontrasting
confidence: 63%
“…Their exploration in obesity is warranted by recent findings indicating that the proinflammatory adipokine leptin and the proinflammatory cytokine macrophage migration inhibitory factor (MIF), both known to be increased in obese humans, 13-17 might stimulate IL-17 production in T cells. 18,19 The aim of this study was to investigate the activity of IL-23/IL-17 and IL-12/IFN-g cytokine axis in obesity, as well as their relationship with the proinflammatory mediators MIF and leptin. The association between cytokine levels and the major anthropometric and metabolic markers of obesity was also explored.…”
Section: Introductionmentioning
confidence: 99%
“…While most investigators reported significant increases in the serum Hcy levels of BD patients compared to healthy individuals, 10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30 some did not find a relationship between BD and serum Hcy levels. 31,32,33,34 …”
Section: Discussionmentioning
confidence: 94%
“…14,15,16,47 In one of these studies including 30 ankylosing spondylitis patients, no significant differences were found between the serum leptin levels of patients with and without a history of uveitis. 47 In another study comparing patients with active Vogt-Kayanagi-Harada syndrome, patients with the inactive disease and healthy individuals, elevated serum leptin levels were found in patients with active disease.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have focused on the important role of Th17 T cells in the initiation and maintenance of VKH,4 and on the pathogenic role of leptin, an adipocytokine that promotes the production of Il-17 and IFN-gamma 5. TNFα increases the production and release of leptin by adipocytes,6 and this pathway might be a likely basis to explain the efficacy of infliximab in patients with VKH.…”
Section: Patientmentioning
confidence: 99%